Successful Treatment of a Patient With Brain Metastasis From Ovarian Cancer With BRCA Wild Type Using Niraparib: A Case Report and Review of the Literature - Zhang, Zhenhua; Xu, Muying; Sakandar, Abbas; Du, Xiuju; He, Huailin; He, Wenfeng; Li, Dan; Wen, Qinglian (Frontiers in Oncology, 2022)
ABSTRACT: Background: Brain metastases from ovarian cancer are extremely rare and have a very poor prognosis. A multimodal approach (surgery combined with radiotherapy and chemotherapy) yields the best results in reducing neurological symptoms and prolonging survival. Unfortunately, not every patient receives a complete multimodal treatment due to their individual factors. Poly(ADP-ribose) polymerase (PARP) inhibitors have emerged as a maintenance treatment option for recurrent ovarian cancer. Using PARPi may prolong the overall survival in patients with Brain metastases recurrent ovarian cancer. Case presentation: We report a case of advanced ovarian cancer without any germline or somatic BRCA mutation. At 21 months later, after reduction surgery and adjuvant chemotherapy, she was diagnosed with brain metastasis. Then, due to her physical fitness and economic situation, she did not receive any radiotherapy or chemotherapy but only received surgical debulking of the brain metastasis and niraparib maintenance treatment. Up to now, she has achieved a good treatment response, and the PFS is 29 months. Conclusion: Based on our patient's response, PARP inhibitors as a single agent can probably be considered in patients with brain metastasis from ovarian cancer without BRCA mutation who cannot tolerate radiotherapy and chemotherapy.